Experimental results of a developed single-phase thyristor switched capacitor - Exposto, Bruno Fernandes (2012)
In this paper are presented simulation and experimental results of a developed single-phase Thyristor Switched Capacitor (TSC), when it is compensating the power factor at the fundamental frequency (displacement power factor) of an electrical system with distorted voltage. The developed single-phase TSC can produce reactive capacitive power with 3 different values. The Thyristor Switched Capacitor is a type of equipment capable of compensating inductive reactive power at the fundamental frequency, without causing voltage and current transients when it is turned-on. However, it can be observed in this paper that in situations where the voltage is distorted, the TSC produces harmonic currents, which is extremely harmful to the electrical system. The capacitor banks used in industries for power factor correction presents the same problem when voltages are distorted.